MiR-142-3p regulates cortical oligodendrocyte gene co-expression networks associated with tauopathy. Issue 1 (8th February 2021) - Hinman, Jason D; Ngo, Kathie J; Kim, Deborah; Chen, Cidi; Abraham, Carmela R; Ghanbari, Mohsen; Ikram, M Arfan; Kushner, Steven A; Kawaguchi, Riki; Coppola, Giovanni; Goth, Kerstin; Bellusci, Saverio; et al.
Abstract: Oligodendrocytes exist in a heterogenous state and are implicated in multiple neuropsychiatric diseases including dementia. Cortical oligodendrocytes are a glial population uniquely positioned to play a key role in neurodegeneration by synchronizing circuit connectivity but molecular pathways specific to this role are lacking. We utilized oligodendrocyte-specific translating ribosome affinity purification and RNA-seq (TRAP-seq) to transcriptionally profile adult mature oligodendrocytes from different regions of the central nervous system. Weighted gene co-expression network analysis reveals distinct region-specific gene networks. Two of these mature myelinating oligodendrocyte gene networks uniquely define cortical oligodendrocytes and differentially regulate cortical myelination (M8) and synaptic signaling (M4). These two cortical oligodendrocyte gene networks are enriched for genes associated with dementia including MAPT and include multiple gene targets of the regulatory microRNA, miR-142-3p. Using a combination of TRAP-qPCR, miR-142-3p overexpression in vitro, and miR-142- null mice, we show that miR-142-3p negatively regulates cortical myelination. In rTg4510 tau-overexpressing mice, cortical myelination is compromised, and tau-mediated neurodegeneration is associated with gene co-expression networks that recapitulate both the M8 and M4 cortical oligodendrocyte gene networks identified from normal cortex. We further demonstrate overlapping gene networks in mature oligodendrocytes present in normal cortex, rTg4510 and miR-142- null mice, and existing datasets from human tauopathies to provide evidence for a critical role of miR-142-3p -regulated cortical myelination and oligodendrocyte-mediated synaptic signaling in neurodegeneration. Graphical abstract: